Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.5433/1679-0359.2012v33n3p997
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of entomopathogenic nematodes (Rhabditida: Steinernematidae and Heterorhabditidae) for the control of Diatraea saccharalis in greenhouse

Abstract: The sugarcane borer, Diatraea saccharalis, makes tunnels in the cane stalk, causing weight loss, as well as bud death, impairing germination. The weakened stalks are also more prone to breakage by wind, and in young plants the inner whorl of the leaves can die, resulting in a condition known as "dead heart". Chemical control is used, but with low efficiency. This work was designed to test biological control of D. saccharalis using entomopathogenic nematodes (NEPs). Two trials in the greenhouse were performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…On the other hand, when the adjuvants Joint ® oil and Gotafix ® (Fig. 9.3) were tested in combination with EPNs against D. saccharalis, no difference was detected compared with a no-adjuvant control (Bellini & Dolinski, 2012).…”
Section: Improved Methods Of Applicationmentioning
confidence: 99%
“…On the other hand, when the adjuvants Joint ® oil and Gotafix ® (Fig. 9.3) were tested in combination with EPNs against D. saccharalis, no difference was detected compared with a no-adjuvant control (Bellini & Dolinski, 2012).…”
Section: Improved Methods Of Applicationmentioning
confidence: 99%
“…() reported that IJ penetration rates of Ostrinia nubilalis Hübner were significantly higher for S. carpocapsae and S. feltiae compared with H. bacteriophora HP88 and NJ strains. More recently, Bellini and Dolinski () reported that foliar applications of H. baujard LPP7 and S. carpocapsae all on sugarcane stalks were equally effective at controlling the sugarcane borer, Diatraea saccharalis F.…”
Section: Discussionmentioning
confidence: 99%
“…In a field experiment with leaf application of different strains, with or without addition of adjuvants, Negrisoli et al [93] observed that H. bacteriophora RS107 + adjuvant (sorbitol) was the most effective treatment against Bonagota salubricola (Meyrick) (Lepidoptera: Tortricidae), an important apple tree pest. Bellini & Dolinski [26] also reported the potential of leaf application of EPNs to control the sugarcane borer, Diatraea saccharalis (Fabricius) (Lepidoptera: Crambidae).…”
Section: Applicationmentioning
confidence: 99%